О находке просфорного штампа на месте кораблекрушения X-XI в.в. в Карасанской бухте у мыса Плака в Крыму - Герасимов, В.Е.; Ястршебовска, Э. (Археологический альманах, 2012)
Просфорный штамп, о котором пойдет речь далее, был обнаружен Черноморской подводноархеологической экспедицией во время полевого сезона 2008 года на месте предполагаемого кораблекрушения X-XI в.в. к западу от мыса Плака, к востоку от горы Аюдаг в акватории поселка Карасан на территории Алуштинского городского совета находящегося на глубине от 6 до 10 метров пологого участка морского дна размером 30х100 м. This is the publication of an early Medieval bread stamp with a cross motif that was found in 2008 during the underwater investigations by the joint expedition of the Crimean Branch of Institute of Archaeology of the Ukrainian National Academy of Science and the Institute of Archaeology of the University of Warsaw near the village Karasan, Crimea. Similar stamps from the eastern Mediterranean are discussed, with a short comment on their function in the orthodox church.